SOX10, GATA3, GCDFP15, Androgen Receptor, and Mammaglobin for the Differential Diagnosis Between Triple-negative Breast Cancer and TTF1-negative Lung Adenocarcinoma - Laurent, Elodie; Begueret, Hugues; Bonhomme, Benjamin; Veillon, Rémi; Thumerel, Matthieu; Velasco, Valérie; Brouste, Véronique; Hoppe, Stéphanie; Fournier, Marion; Grellety, Thomas; MacGrogan, Gaëtan (The American journal of surgical pathology, 2019)
Triple-negative breast cancer (TNBC) patients have an increased risk of developing visceral metastases and other primary nonbreast cancers, particularly lung cancer. The differential diagnosis of TNBC metastases and primary cancers from other organs can be difficult due to lack of a TNBC standard immunoprofile. We analyzed the diagnostic value of estrogen receptor, progesterone receptor, human epidermal growth factor receptor, thyroid transcription factor-1 (TTF1), Napsin A, mammaglobin, gross cystic disease fluid protein 15 (GCDFP15), Sry-related HMg-Box gene 10 (SOX10), GATA-binding protein 3 (GATA3), and androgen receptor in a series of 207 TNBC and 152 primary lung adenocarcinomas (LA). All tested TNBCs were TTF1 and Napsin A-negative. When comparing TNBC and TTF1-positive or negative LA, SOX10 had the best sensitivity (62.3%) and specificity (100%) as a marker in favor of TNBC compared with LA, irrespective of TTF1 status (P<0.0001). GATA3 had moderate sensitivity (30.4%) and excellent specificity (98.7%) and misclassified only 2/152 LA (1.3%). GCDFP15 had a moderate sensitivity (20.8%) and excellent specificity (98%) and misclassified only 3/152 (2%) LA. Mammaglobin and androgen receptor had moderate sensitivities (38.2% and 30%), good specificities (81.6% and 86%), and misclassified 28/152 and 21/152 LAs, respectively. In multivariate analysis, the best markers, enabling the distinction between SOX10-negative TNBC and TTF1 and Napsin A-negative LA were GATA3 (odds ratio=33.5; 95% confidence interval, 7.3-153.5; P<0.0001) and GCDFP15 (odds ratio=31.7; 95% confidence interval, 6.9-145.6; P<0.0001). Only 13/207 (6.3%) TNBC cases did not express any aforementioned marker. On the basis of our results, the best sequential immunohistochemical analysis to differentiate TNBC from TTF1-negative LA is first SOX10 followed by GATA3, and finally GCDFP15. This order is important in the diagnostic workup of small biopsies from lung nodules in women with a previous history of TNBC.